2020
DOI: 10.3390/v12030257
|View full text |Cite
|
Sign up to set email alerts
|

Priming Melon Defenses with Acibenzolar-S-methyl Attenuates Infections by Phylogenetically Distinct Viruses and Diminishes Vector Preferences for Infected Hosts

Abstract: Plant virus management is mostly achieved through control of insect vectors using insecticides. However, insecticides are only marginally effective for preventing virus transmission. Furthermore, it is well established that symptoms of virus infections often encourage vector visitation to infected hosts, which exacerbates secondary spread. Plant defense elicitors, phytohormone analogs that prime the plant immune system against attack, may be a viable approach for virus control that complements insecticide use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
(73 reference statements)
1
6
1
Order By: Relevance
“…Similar results were also reported for tobacco and melon plants that were primed by acibenzolar-S-methyl, a commercially available mimic of the phytohormone SA, before being challenged with Tomato spotted wilt virus, Cucumber mosaic virus or Cucurbit yellow stunting disorder virus (Kenney, Grandmont, & Mauck, 2020;Mandal et al, 2008). Our results also indicated that Z-3-HOL pre-exposure significantly reduced whitefly vector visitation time (1 hr) and settling time (2-24 hr) (Figure 1d).…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were also reported for tobacco and melon plants that were primed by acibenzolar-S-methyl, a commercially available mimic of the phytohormone SA, before being challenged with Tomato spotted wilt virus, Cucumber mosaic virus or Cucurbit yellow stunting disorder virus (Kenney, Grandmont, & Mauck, 2020;Mandal et al, 2008). Our results also indicated that Z-3-HOL pre-exposure significantly reduced whitefly vector visitation time (1 hr) and settling time (2-24 hr) (Figure 1d).…”
Section: Discussionsupporting
confidence: 87%
“…The insecticides cyantraniliprole and terpene constituents of Chenopodium ambrosioides near ambrosioides extract also reduced the number of whitefly adults on seedlings, although cyantraniliprole alone reduced virus incidence. Acibenzolar-S-methyl, a salicylic acid analog, does not have insecticidal properties but is known to induce plant defenses against viruses by activating the salicylic acid pathway [58][59][60]. While fewer adult whiteflies were observed in the acibenzolar-Smethyl treatment compared with the non-treated control in our study, the former did not reduce virus incidence in squash seedlings.…”
Section: Discussioncontrasting
confidence: 64%
“…While fewer adult whiteflies were observed in the acibenzolar-Smethyl treatment compared with the non-treated control in our study, the former did not reduce virus incidence in squash seedlings. It is possible that the timing of our acibenzolar-S-methyl application could be optimized to improve virus protection [59], or that multiple applications may be necessary for suppressing CuLCrV-induced symptoms on squash seedlings [60]. The greenhouse experiment in this study demonstrated that seedling infection in open greenhouses could be minimized with the use of IEN in conjunction with insecticides.…”
Section: Discussionmentioning
confidence: 88%
“…So controlling this preference by some chemical signal would be very helpful to improve crop yield. For example, in [19], they take advantage of knowledge about elicitors that prime the plant immune system against attack to test the effect of a commercial elicitor on infection rates, finding that artificially boosting immunity delayed disease and decreased symptoms. 1.…”
Section: Simulationsmentioning
confidence: 99%